Al-Mushkilāt fī al-Tamyīz bayna al-Tarkīb al-Iḍāfī wa-al-Tarkīb al-Naʿtī fī al-Qirā’ah li-Ṭalabat al-Jāmiʿah - M. ‘Athif Audl Ramadlan; Masngut Masngut (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2022)
There are still many students in the Arabic Language Teaching Department at Walisongo State Islamic University Semarang who still face the difficulty of distinguishing between phrase and adjective structures in reading skill. There must be many reasons that cause difficulties and problems in distinguishing between phrase and adjective structures. The objectives of this research are: To find out the causes of problems in distinguishing between phrase and adjective structures in reading skill for students of the Arabic Language Teaching Department in 2017 at Walisongo State Islamic University Semarang and to know the appropriate solutions to overcome the problems. The researcher held a survey study with the statistical community of all students of the Arabic Language Teaching Department in 2017, with a number of 70 students. The researcher used the test and interview to collect data. The results of this research are that one of the reasons for its problems is the lack of control over the rules of auxiliary structure and the adjective structure and the differences between them, the lack of practice in determining the phrase and adjective structures and distinguishing between them in Arabic texts, the lack of practice in reading Arabic texts that contain the phrase and adjective structures, the lack of vocabulary, and the lack of understanding Vocabulary Genres. As for the solutions to the problems, they are supposed to the understand the rules of phrase and adjective structures and the differences between them, a lot of practice in identifying and differentiating between them in Arabic texts, more rehearsing in reading Arabic texts, a lot of reading Arabic texts so that students get a lot of vocabulary, and a lot of understanding the types of vocabulary.